TANGGUNG JAWAB PENGUSAHA BUS TRANS METRO PEKANBARU (TMP) TERHADAP KERUGIAN PIHAK KETIGA YANG MENJADI KORBAN KECELAKAAN DITINJAU DARI KITAB UNDANG-UNDANG HUKUM PERDATA - Wibowo, Eri Surya; Hasanah, Ulfia; ', Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
traffic accident is an incident on the road that can not be known when and where it will happen. Traffic accidents are a matter that could give rise to rights and obligations for each party for damages. Traffic accident that causes damage to a third party in the civil responsibility of employers or owners dikerenakan bus driver or bus wardens to supervise. It can be seen from the provisions of Article 1367 of the Civil Code and Article 234 paragraph (1), (2) of Law No. 22 of 2009 on Road Traffic and Road Transport. Legal protection against third parties is the protection of the rights of third parties who are victims of accidents, these rights set forth in the provisions of Article 240 of Law No. 22 of 2009.Keywords : Responsiability – Businessman – Compensation - Third Party